The joys and frustrations of life as an embedded researcher: Findings from a diary study of researchers embedded within local authority public health teams in England. - Claire Stansfield; Dylan Kneale; Rachael C Edwards (PLoS ONE, 2025)
Embedded researcher interventions endeavour to facilitate culture changes in the production and use of research, so that research is contextually relevant for informing local policies and practices. However, the daily life of embedded researchers is poorly understood, as is their perceptions of working in a role intersecting research with local government settings. An embedded researcher intervention across English local authority public health teams provided an opportunity to understand what happens within these roles and which activities are undertaken. We describe the findings from a daily diary survey completed by embedded researchers for one week over two waves, comprising open-ended and closed questions (Nine participants in wave 1, of which five completed wave 2). Free-form entries were thematised using template analysis and quantitative data analysed through descriptive statistics. The diaries provided a valuable snapshot into a varied working life. Activities included: attending meetings; organising or requesting information; presenting evidence and data-preparation; collecting or analysing data; and providing information or research expertise. Embedded researchers require strong relational skills to collaborate with stakeholders in academia, community, local government and research funders on a range of topics. Participants reported both feelings of satisfaction and disappointment, and some described isolation. There was positive expectation that their activities gradually enhance useful public health research, though require time and system changes. Embedded researchers require support from stakeholders at all levels to maximise the potential benefits of their roles.